2016
DOI: 10.1039/c6gc00557h
|View full text |Cite
|
Sign up to set email alerts
|

Microwave-assisted direct oxidative synthesis of α-ketoamides from aryl methyl ketones and amines by a water soluble Cu(i)-complex

Abstract: A stable and isolable Cu(i) complex has been identified for the direct oxidative synthesis of α-ketoamides in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 48 publications
(18 citation statements)
references
References 66 publications
(12 reference statements)
0
18
0
Order By: Relevance
“…Based on the above results and some relevant publications,,, a plausible mechanism was proposed, as shown in Figure . With UV at λ=210 nm, molecular oxygen in the air was transformed to ozone (O 3 ), which then underwent gradual dissolution in aqueous media, and decomposed immediately upon meeting with hydroxyl anion (OH − ) to form superoxide radical anion (O 2 .− ), see Figure .…”
Section: Resultsmentioning
confidence: 66%
“…Based on the above results and some relevant publications,,, a plausible mechanism was proposed, as shown in Figure . With UV at λ=210 nm, molecular oxygen in the air was transformed to ozone (O 3 ), which then underwent gradual dissolution in aqueous media, and decomposed immediately upon meeting with hydroxyl anion (OH − ) to form superoxide radical anion (O 2 .− ), see Figure .…”
Section: Resultsmentioning
confidence: 66%
“…They have concluded that the optimal reaction conditions achieved using catalytic amount (10 mol %) of NiCuFe 2 O 4 nanoparticles (NiCuFe 2 O 4 NPs) in the presence of silica gel, the resulting mixture was heated in a microwave oven at 100 • C for 4 min to obtain the desired products in excellent yields, Scheme 64. Under controlled microwave irradiation technique, Shankaraiah and coworkers have developed novel copper(I)-complex [bis(tetrabutylammonium)di-µ-iodo-diiododicuprate(I)] for the synthesis of α-ketoamides starting from aryl methyl ketones and amines [125]. The reaction proceeds smoothly using a catalytic amount (20 mol %) of the copper(I)-complex (Cu(I)-complex) in the presence of molecular oxygen as oxidizing agent, and water as solvent, the reaction mixture was then heated in a microwave oven at 60 • C for 10 min to produce the target compounds in moderate to excellent yields, Scheme 66.…”
Section: Scheme 62mentioning
confidence: 99%
“…Also, the impact of electronic nature of azide and alkyne derivatives in the formation of functionalized 1,2,3‐triazoles cannot be ignored. In the course of time, we identified a stable and isolable, water soluble bis[(tetrabutylammonium) di‐ μ ‐iodo‐diiododicuprate(I)] 71 complex . We envisioned a Cu(I) catalytic system that would generate 1,2,3‐triazolo‐tetrahydro‐β‐carboline derivatives in excellent yields.…”
Section: 3‐dipolar Cycloadditionmentioning
confidence: 99%